Proposal For A Method Of Comparing CO2 Emissions For Helicopters - Jimenez, J.; Pepe, V.; Routhieau, V.; Ripolles, F.; Basset, P. M. (My University, 2025)
Major aviation organizations aim for net-zero carbon dioxide emissions by 2050. Even though helicopters represent under 1% of global aviation's 2-3% contribution to worldwide CO2, reducing their emissions is essential to fulfill aviation's commitments and prepare for future regulations. Due to the specific missions of helicopters, standard metrics from automotive and fixed-wing aircraft industries are unsuitable. This article presents the methodology for defining a CO2 metric for helicopters. Several metrics have been challenged before final recommendation. The first one consists of computing the net CO2 emitted on a given mission, directly from the fuel burn. The other approaches introduce dimensionless factors in order to relate the CO2 emission to a "given service", which naturally increases with the helicopter's carrying capacity. This capacity is analyzed in two ways: by payload for cargo missions, the difficulties being the alignment of configuration and by seating capacity for passenger transport missions, the advantage being the use of verifiable public data.